Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.molp.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Genome-wide Association Study Identifies Genomic Regions and Candidate Genes for Important Agronomic Traits in Wheat

Abstract: Wheat (Triticum aestivum) is a major staple food crop worldwide. Genetic dissection of important agronomic traits is essential for continuous improvement of wheat yield to meet the demand of the world's growing population. We conducted a large-scale genome-wide association study (GWAS) using a panel of 768 wheat cultivars that were genotyped with 327 609 single-nucleotide polymorphisms generated by genotyping-by-sequencing and detected 395 quantitative trait loci (QTLs) for 12 traits under 7 environments. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
121
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 84 publications
(85 reference statements)
15
121
0
Order By: Relevance
“…In such cases, projection onto a genetic map serves as a complementary approach. Owing to the increasing number of different types of genetic markers, a high-density consensus genetic map that compiles 7352 markers has been reported [130] and is used here for the projection of kernel hardness-associated QTLs ( Figure S1, Table S2). While the QTLs subjected to fewer studies can be located on the consensus genetic map, both QTL locations on the genetic and genome maps are consistent.…”
Section: Dissecting the Genetic Loci Controlling Wheat Kernel Hardnessmentioning
confidence: 99%
“…In such cases, projection onto a genetic map serves as a complementary approach. Owing to the increasing number of different types of genetic markers, a high-density consensus genetic map that compiles 7352 markers has been reported [130] and is used here for the projection of kernel hardness-associated QTLs ( Figure S1, Table S2). While the QTLs subjected to fewer studies can be located on the consensus genetic map, both QTL locations on the genetic and genome maps are consistent.…”
Section: Dissecting the Genetic Loci Controlling Wheat Kernel Hardnessmentioning
confidence: 99%
“…Through advances in next generation sequencing, identification of major QTLs regulating specific drought responses has been made possible, via the development of large numbers of genetic markers such as single nucleotide polymorphisms (SNPs) and insertion-deletions (InDels), thereby opening the doors for an efficient way to improving drought tolerance in cereal crops [89]. Additionally, large-scale genome-wide association studies (GWAS) have been conducted to detect genomic regions and candidate genes for various agronomic traits, including drought tolerance in cereals [13,136,137]. Resultantly, hundreds of studies reporting thousands of major drought-responsive genes and QTLs in cereal grain crops can be found in the literature, including those for maize [13,[138][139][140], rice [12,13,105,138,141,142], wheat [13,31,137,138,143], sorghum [138,144,145], barley [138,146], and pearl millet [136,147,148].…”
Section: Qtl Mapping For Drought Tolerance In Cerealsmentioning
confidence: 99%
“…Going forward, MAS remains a useful tool for major QTL, whereas QTL cloning is increasingly becoming a more routine activity. This has been necessitated by increased use of high-throughput sequencing, precise phenotyping and identification of appropriate candidate genes through omics approaches [89,136,137]. Cloned QTL facilitate a more targeted search for novel alleles and will offer novel insights for genetic engineering of drought resilient cereal crops [13].…”
Section: Qtl Mapping For Drought Tolerance In Cerealsmentioning
confidence: 99%
“…Using the genome browser of IWGSC RefSeq v1.0, we found that the SNP is located ~255 kb upstream of the major STB resistance gene Stb6. Linkage disequilibrium (LD) in wheat is large in comparison to other cereals due to its self-pollinating nature (Cavanagh et al 2013;Wang et al 2014;Pang et al 2020). Pang et al (2020) showed that the average genome-wide LD block size in wheat is around 4.2 Mb.…”
Section: Genome Wide Association Study Identifies Stb6 As the Major Smentioning
confidence: 99%